Principles of implementation of organ preservation activities in a donor hospital - S. Y. Pushkin; A. S. Navasardian; A. A. Selutin; K. K. Gubarev; V. E. Aleksandrova; B. I. Yaremin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The implementation of organ transplantation programs in our country is far from perfect. Many regions do not have transplantation centers, in many regions the work on organ donation is not carried out. Intensification of this vital work is of key importance – the need for organ transplantation remains unfulfilled in many regions of the Russian Federation by 70–90 %. The activity on organ donation must be realized with strict administrative control and administrative stimulation. It does not represent the sphere of interests of particular transplantologists. It is a strategically important task, the implementation of which should be carried out at the state level. The key importance in the implementation of organ transplantation program is the hospital where the potential donor is located, identified and accompanied. In the literature and daily practice the outdated term “donor base” is often used, the use of which we consider unacceptable. The donor hospital is a spring, a source of life, the work in which has a key, starting character.